Penyakit Tidak Menular Melalui GEMPITA : Gerakan Memanfaatkan Sampah Organik Untuk TOGA - Syahla Farida; Ai Kurniasih; Mutiya Rahmah; Marshanda Darianti; E. Wipa Wildatu Saniah; Rafi Ashari Nuryana; Lutfi Hilman Abdullah; Andy Muharry (Pelayanan Unggulan : Jurnal Pengabdian Masyarakat Terapan, 2024)
Non-Communicable Diseases (NCDs) are a serious health challenge in Indonesia, especially in Setiajaya Village, where low public awareness of NCD risk factors makes the condition worse. This study aims to increase public knowledge and awareness regarding NCDs through the "GEMPITA" program which teaches the use of organic waste to grow Family Medicinal Plants (TOGA). The community service method was used, involving planning, direct education, and pre-test and post-test based evaluation. The results showed a significant increase in participant understanding (p-value = 0.001) with 92% of participants showing increased knowledge. Enthusiasm and active interaction during the education session were indicators of success. These results suggest that the use of waste for TOGA can be implemented as a community step in preventing NCDs. The implications of this study point to the importance of expanding this education program to other areas and involving various stakeholders so that the impact is more significant.